Academic Gratitude as a Mediator between Psychological Well-Being and Academic Buoyancy among college students in West Java - Nurul, Wardhani; Hendriati, Agustiani; Ida Juliana, Hutasuhut; Ahmad Gimmy, Prathama Siswad (Frontiers Research Foundation, 2026)
Introduction: This study aims to examine the relationships among Psychological Well-Being, Academic Gratitude, and Academic Buoyancy among students in Indonesia, and to assess whether Academic Gratitude acts as a partial mediator in these relationships.